2019
DOI: 10.24193/subbchem.2019.3.07
|View full text |Cite
|
Sign up to set email alerts
|

Thin layer photocatalysts of TiO2-Ag composites

Abstract: BORBÁLA TEGZE a , EMŐKE ALBERT a , BOGLÁRKA DIKÓ a , JÁNOS MADARÁSZ b , GYÖRGY SÁFRÁN c , ZOLTÁN HÓRVÖLGYI a, * ABSTRACT. Mesoporous TiO2 coatings were prepared by sol-gel dipcoating method on glass and SiO2 coated glass substrates. They were modified with silver by two different methods: impregnation of as-prepared coatings in AgNO3 aqueous solution; coating deposition from precursor sols containing AgNO3. Transmittance spectra, refractive index, layer thickness and porosity were determined by UV-Vis spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Indirect band gap was assumed, and the determined band gap energy was found to be similar for c-TiO 2 and p-TiO 2 samples (3.39 and 3.38 eV, respectively), while the Ag modified coatings had a slightly lower band gap energy (3.34 eV for p-TiO 2 (1Ag) and 3.33 eV p-TiO 2 -Ag coatings). This suggests that TiO 2 is present mainly in its anatase crystal phase in these samples, in accordance with the results of our previous publication [25], in which XRD measurements were carried out on model powder samples of the c-TiO 2 , c-TiO 2 (1M), c-TiO 2 (0.03M) and p-TiO 2 -Ag type coatings, and where it was found that anatase phase is present in 90-100 wt %, while rutile phase is present in 0-10 wt %, and the crystallite size was determined to be~12 nm.…”
Section: Characterization Of Tio 2 and Tio 2 -Ag Coatingssupporting
confidence: 93%
See 2 more Smart Citations
“…Indirect band gap was assumed, and the determined band gap energy was found to be similar for c-TiO 2 and p-TiO 2 samples (3.39 and 3.38 eV, respectively), while the Ag modified coatings had a slightly lower band gap energy (3.34 eV for p-TiO 2 (1Ag) and 3.33 eV p-TiO 2 -Ag coatings). This suggests that TiO 2 is present mainly in its anatase crystal phase in these samples, in accordance with the results of our previous publication [25], in which XRD measurements were carried out on model powder samples of the c-TiO 2 , c-TiO 2 (1M), c-TiO 2 (0.03M) and p-TiO 2 -Ag type coatings, and where it was found that anatase phase is present in 90-100 wt %, while rutile phase is present in 0-10 wt %, and the crystallite size was determined to be~12 nm.…”
Section: Characterization Of Tio 2 and Tio 2 -Ag Coatingssupporting
confidence: 93%
“…The simplest and most often used way to prepare TiO 2 -Ag composites with this method is to add AgNO 3 (or other precursor containing silver ions) to the precursor sol [21][22][23]. Another promising possibility is to modify the as-prepared mesoporous coatings by impregnation in AgNO 3 solution, followed by post-treatments step(s) in which the silver ions are reduced [24][25][26][27]. These post-treatment steps most often include heat treatment [24,25] or UV irradiation [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the development of the composite materials with specific characteristics for the most diverse applications is in the continuous attention of the scientific community and industrial developers [3]. Thus, developments of ceramic composites [4] for various medical applications [5,6], electrodes for electrochemical synthesis [7], thin layers for photocatalysis [8], polymer-based composites with various fillers [9 -16] are reported with uses including the electrical engineering field [17][18][19][20], etc.…”
Section: Introductionmentioning
confidence: 99%